Efeitos do pastejo e desmatamento sobre a diversidade funcional de comunidades vegetais na região semiárida brasileira - Lima, Raquel Bruna Chaves de (Universidade Federal Rural do Semi-Árido, 2018)
Livestock associated with deforestation for conversions of extensive areas into pasture are factors that cause large impacts to soil degradation and reductions in native vegetation of global ecosystems. In addition to changes in species diversity, the overgrazing can cause loss of functional diversity with the reduction of interspecific variability of characteristics and increase of functional convergence. However, there are few studies on the impacts of these anthropogenic disturbances on the functional diversity of the Caatinga plant communities, which is the main objective of this work. The study was carried out in farms located in the municipality of Angicos/RN, in areas previously identified under different degrees of grazing and deforestation. In each area the tree / shrub and herbaceous species were sampled. In the tree and shrub plants, the following functional traits were measured: height, total and specific leaf area, thickness, leaf resistance, as well as leaf nitrogen and phosphorus concentrations. The individuals / species sampled were also classified according to the presence of spines, pollination and dispersion. In the herbaceous plants the height, leaf area and height were measured for clonality, shape of growth and life-form. Changes in functional composition were assessed through communities' CWM (community weighted mean) of traits and functional diversity was quantified using the Rao quadratic entropy index and the results obtained were compared to null models to detect if there are convergence or functional divergence patterns. The results showed low tree and herbaceous species richness and a positive correlation with functional diversity. In the tree community, high grazing in the non-deforestation fragment favored plants with large, resistant leaves, greater specific leaf area, and leaf nitrogen while it was registered an abundance of small shrubs under intermediate grazing and higher proportion of thorns under high grazing due to dominance of Mimosa tenuiflora species. On the other hand, the increase of grazing causes functional convergence of the species through environmental filtering whereas under low grazing the traits tend to be divergent, indicating greater interspecific competition and limiting similarity. The herbaceous community presented reductions in leaf area and height with the increase of the grazing. terophyte and non-clonal species are generally predominant, with an increase in the frequency of stoloniferous grasses in fragments without deforestation with high grazing intensity. The functional diversity of the herbaceous species showed a decrease in the non-deforested fragment with low grazing and indicated a divergence of the functional traits in the non-deforested sites. These results point to different effects of environmental filters on the functional diversity of arboreal and herbaceous species
Keywords: Caprinocultura; Filtragem ambiental; Florestas secas; Caatinga; Traços funcionais; goat breeding; deforestation; dry forests; Caatinga; functional traits; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA